Asia falling? making sense of the Asian currency crisis and its aftermath (Singapore ; Sydney McGraw-Hill, 1998)
Veteran Asia-watcher Callum Henderson - Standard & Poor's senior authority on the Asian currency market and one of the few insiders to counsel caution during the heady boom days - delivers a first-hand examination of the political and economic events that led to Asia's currency crisis. Written with clarity and objectivity, and supported by fact-filled case studies of Thailand, Indonesia, the Philippines, and Malaysia, this book goes beyond the hyperbole and the punditry to give investors an in-depth, country-by-country analysis of the crisis, and forecast the economic effects on the region; provide policy-level political analysis on governmental actions and reactions that led to Asia's ongoing currency crisis; and outline specific opportunities resulting from the Asian currency crisis and its consequent economic impact.
1. The Objective - Growth at Any Price -- 2. The Hype - Emerging Market Fever -- 3. The Warning - Dollar-Yen Rebounds -- 4. The Precedent - Mexico -- 5. The Catalyst - Thailand -- 6. The Meltdown - One by One -- 7. The Aftermath - Recrimination -- 8. The Banker - Japan's Exposure -- 9. The Fundamentals - Problems, Challenges, and Opportunities -- 10. The Rescue - The IMF, Then Rubin, Then Soros -- 11. The Danger - China Unscathed or the Next Crisis?
Includes bibliographical references.
Keywords: Foreign exchange rates -- Asia; Asia -- Economic conditions; ASEAN; Asia; Asian financial crisis; Economic conditions; Exchange rates; Foreign exchange markets; International Monetary Fund; Macroeconomic policy; Overseas item